Strengthening Early Detection Of Pregnancy Risks Via An Intelligent System In Rural Communities - Rian Ardianto; Deny Nugroho Triwibowo; Riska Suryani; Atina Salamah (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Maternal health is a crucial indicator of public health quality, yet monitoring in rural areas is often conducted manually with low technological literacy. This study aims to evaluate the effectiveness of technology-based education using a web-based application in improving health cadres' knowledge and skills regarding pregnancy danger signs, maternal and child nutrition, and early pregnancy risk detection. The method used is a participatory approach based on community engagement adapted with a design sprint framework, encompassing understand, define, develop, deliver, and evaluate stages. The activity involved 30 health cadres in Karangrau Village through counseling, discussions, and web-based application simulations. Evaluation used a descriptive Likert-scale pre-test and post-test questionnaire. Results showed a significant improvement in participants' understanding, with average scores increasing from 89% in the pre-test to 99% in the post-test. The use of a web-based application proved effective in concretely visualizing health data. In conclusion, the integration of participatory education and interactive technology effectively enhances cadre capacity and has the potential to become a sustainable educational model. This program is expected to encourage the utilization of simple technology as a medium for delivering health information at the community level.